Prevalence of heavy episodic drinking and associated factors among adults residing in Arba Minch health and demographic surveillance site: a cross sectional study - Befikadu Tariku Gutema; Adefris Chuka; Gistane Ayele; Eshetu Zerhun Tariku; Zeleke Aschalew; Alazar Baharu; Nega Degefa; Mekdes Kondale Gurara (BMC, 2020)
Abstract Background Alcohol consumption is associated with different types of illnesses; particularly heavy episodic drinking is one of the risk factors for the disease burden of alcohol intake. The aim of the study was to assess the prevalence of heavy episodic drinking and associated factors in Arba Minch Health and Demographic Surveillance Site (HDSS). Methods A community-based cross-sectional study was conducted in 2017 among adult residents of Arba Minch HDSS. Using Arba Minch HDSS database, 3368 individuals were selected by simple random sampling techniques. From WHO STEPS instruments, step one was applied for this study. Variables with a p-value of less than 0.10 for bivariate analysis entered into a multivariable logistic regression model to outline the independent predictors of the heavy episodic drinking. To assess the presence of an association between dependent and independent variables, a p-value of less than 0.05 was considered. Results The prevalence of heavy episodic drinking was 13.7% (95% CI: 12.6-14.9). The study has shown that heavy episodic drinking was significantly associated with occupation (daily laborer [AOR = 0.49; 95% C.I: 0.29-0.85] and housewives [AOR = 0.63; 95% C.I: 0.45-0.88] compared with farmers), wealth index (2nd quintiles [AOR =0.55; 95% C.I: 0.41-0.74) and 3rd quintiles [AOR = 0.66; 95% C.I: 0.46-0.93] compared with 1st quintiles), and climatic zone (midland [AOR = 1.80;95% CI: 1.11-2.93), highland [AOR = 1.95;95% CI: 1.19-3.18] compared with lowland). In addition, tobacco use [AOR = 4.28;95% CI: 3.38-5.43], and khat use [AOR = 4.75; 95% CI: 2.66-8.50) were also associated with heavy episodic drinking among the study participants. Conclusions More than one in ten adults reported heavy episodic drinking in the study area. Intervention programs that aim to prevent heavy episodic drinking should be designed appropriately for individuals from lower wealth status, and for highlander.